Apparatus Human Resource Development Strategy through Corporate University of the Agrarian and Spatial Planning/National Land Agency - Ulvi Ratnaningsih Sa'adah; Ridwan Rajab; Firman Hadi Rivai (Journal La Sociale, 2023)
This study aims to formulate the Center for Human Resource Development (PPSDM) strategy of the Ministry of the Agrarian and Spatial Planning/National Land Agency (ATR/BPN) in developing the competence of HR personnel based on the Corporate University strategy. This study uses a qualitative descriptive method with data analysis using the Miles and Huberman model. The results showed that the strategy for implementing the ATR/BPN corporate university was strengthening the legal basis, providing rewards to employees, preparing budgets, strengthening the implementation of the Learning Value Chain, Assigning PPSDM employees to oversee and ensure LVC runs, Development of learning models 70:20:10, Implementation of learning council meeting.